Good Corporate Governance, Struktur Modal, dan Kinerja Keuangan terhadap Harga Saham Perusahaan Sektor Financials - Rosita Diyah Ramadhani; Sigit Puji Winarko; Erna Puspita (STIKes Ibnu Sina Ajibarang, 2025)
There is a large correlation between its economic development and a country’s capital market. The capital market connects individuals with potential investments and helps businesses obtain the necessary financing. The way investors view a company’s growth potential is reflected in its stock valuation. Stock price fluctuations are influenced by several factors, including effective Good Corporate Governance (GCG), capital structure, and financial performance. By examining the impact of GCG, financial performance, and capital structure, this study aims to provide clearer guidelines on how companies in the financial sector of the IDX can influence stock prices from 2020 to 2024. The quantitative method used is multiple linear regression analysis. The study found that stock values ​​were significantly influenced by these three factors, both separately and when combined. These three variables explain a quarter of the variance in stock prices (measured by the Adjusted R² value of 0.256), while the remaining variation is due to variables outside this study. Whether you are an investor or a business leader, these findings can help you make better financial and governance choices and will pave the way for further research.